Análise de risco de enchentes mediante modelos hidrodinâmicos Fuzzy - Castro, Maria Patrícia Sales (2019)
Many of the hydrodynamic problems involving wave propagation along the extension in natural channels are solved through the Saint-Venant equation. In most applications In practice, kinematic and diffuse wave models are applied to rivers to study the propagation of a flood wave in natural channels. These models are derivations of the Wave Model. Dynamics, from simplifications of the Saint-Venant Equations, where some terms are despised. This research aims to apply the Fuzzy Theory in hydrodynamic models wave propagation in natural channels in order to verify the uncertainties and risks in relation to the hydrodynamic parameters present in these models. The introduction of logic fuzzy in the hydrodynamic model, to calculate the membership functions linked to the variables provides an appropriate and promptly effective procedure for the analysis of the risk fields present in the flood wave propagation process. Differential Equations relevant to the models were solved through the Finite Differences being the explicit approximation scheme applied to the dynamic and kinematic wave models, while the implicit approximation scheme was applied to the wave model diffuse. Some specific simulations were also performed for behavior analysis. flood risk and guarantee, depending on the hydraulic and hydrological characteristics of the thus assessing how certain changes in the roughness coefficient, or channel slope, for example, may affect the behavior of the risk function. The results show that the behavior of the dynamic, diffusive and dynamic wave propagation kinematics, as well as the behavior of risk and guarantee functions, are influenced by the hydraulic parameters of the channel. According to the results presented, it was concluded that The application of the Fuzzy Theory in hydrodynamic systems in the evaluation of uncertainties is a viable alternative to determine the risk of flooding and thus be one more support tool in Water Resource Management programs.